Injection molding parameter optimization of titanium alloy powder mix with palm stearin and polyethylene for green defects using taguchi method - Mohamad Nor, Nor Hafiez; Muhamad, Norhamidi; Ismail, M. H.; Jamaludin, Khairur Rijal; Ahmad, S.; Ibrahim, M. H. I. (2009)
This paper outlines the Taguchi Method using L?? (3??) orthogonal array, which is applied to optimize injectin molding parameters in Metal Injection Molding (MIM) process using titanium alloy powder mix with palm stearin and polyethylene. Parameters optimized were injection pressure, injection temperature, powder loading, mold temperature, holding pressure and injection speed. Classical analysis of variance (ANOVA) for the smallest the best signal to noise ratio (S/N) presents the significance of each parameters and interaction. A green defects was assumed to be the quality characteristics (response) and it has been measured using parameter design for discrete data technique. From the ANOVA, the injection pressure has the highest percentage of contribution to the green defects followed by interaction of injection pressure-powder leading and interaction of injection pressure-injection temperature